Reviewing the Palaeoenvironmental Record to Better Understand Long-Term Human-Environment Interaction in Inner Asia During the Late Holocene - Spate, Michael; Leipe, Christian; Motuzaite Matuzeviciute, Giedre (Frontiers in Ecology and Evolution, 2022)
The Middle to Late Holocene spread of agropastoralism throughout Eurasia not only subjected domesticated taxa to stressors associated with novel environments but also induced changes in these environments following the introduction of these social-ecological systems. The mountainous region of Inner Asia comprises various steppe, meadow, and forest landscapes where zooarchaeological evidence suggests occupation by herding populations as early as 7,000 years Before Present (BP). Recent archaeobotanical findings indicate the introduction of cropping and the development of agropastoralism around 4,500 BP. Here, we review and synthesize palaeoenvironmental studies and data to examine anthropogenic impacts and modifications of these landscapes. From around 4,000 BP, we find significant changes in palynomorph, charcoal, sediment, and other proxy data, related to the introduction of agriculture to the region, with later intensifications in land use indicators at around 2,000 and 1,000 BP. We note that these impacts are not uniform or continuous through and across the records and may be evidence of shifting phases of occupation and landscape management. This temporal and spatial variability may also be a response to shifts in moisture availability due to long-term Holocene changes in the intensity of the summer monsoon and Westerly circulation systems. Changes in arboreal pollen indicate the development of intensified use of forest resources in the region, which we identify as a topic for future investigation. Based on these data, we stress the long-term human paleoecology in the study area and argue that traditional agropastoralist systems should be considered in future programs of landscape conservation in the region. This study also emphasizes the importance of future local scale multiproxy studies into past anthropogenic changes within the Inner Asian landscape.